A POTENTIAL APPROACH TO THE USE OF ARTIFICIAL INTELLIGENCE IN TRADEMARK VERIFICATION PROCESS - Napitupulu, Novita Sartika Elisabeth; Situmorang, Yan Putra Jalo (NOMOI Law Review, 2024)
Artificial Intelligence (AI) is undeniably impacting many aspects of life, including legal fields. Many countries are now focused on developing AI in many sectors, such as governmental services. In relation to the plan of the Government of Indonesia to provide faster public services, AI can be expected to be a catalyst and support in the field of the Intellectual Property Rights verification process, specifically trademark. By now, the process may take several times to arrive at the final decision before the certificate of IP Rights ownership is given to the applicant. This is due to the necessity of the details that need to be checked to guarantee the originality of the application of the IP rights. This paper will discuss the possibility of how AI can be a helpful breakthrough to innovate in assisting the intellectual property rights verification process under the supervision of the Ministry of Law and Human Rights in Indonesia.